2006
DOI: 10.1016/j.jaci.2006.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Role of small airways in asthma: Investigation using high-resolution computed tomography

Abstract: Small airways are an important therapeutic target in asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 51 publications
7
108
1
3
Order By: Relevance
“…These authors reported that lung attenuation was significantly higher in asthmatics; interestingly, air trapping scores were higher after metacholine challenge, but air trapping only partially disappeared after salbutamol inhalation [59], suggesting that small airways constriction persisted. In another study, the percentage of lung field occupied by low attenuation area at inspiration showed some correlation with FEV1/FVC, suggesting an association between asthma severity and small airways [60]. Furthermore, MITSUNOBU et al [61] reported decreased CT lung density during asthma exacerbations.…”
Section: Imaging Techniques In the Evaluation Of Small Airways In Obsmentioning
confidence: 93%
“…These authors reported that lung attenuation was significantly higher in asthmatics; interestingly, air trapping scores were higher after metacholine challenge, but air trapping only partially disappeared after salbutamol inhalation [59], suggesting that small airways constriction persisted. In another study, the percentage of lung field occupied by low attenuation area at inspiration showed some correlation with FEV1/FVC, suggesting an association between asthma severity and small airways [60]. Furthermore, MITSUNOBU et al [61] reported decreased CT lung density during asthma exacerbations.…”
Section: Imaging Techniques In the Evaluation Of Small Airways In Obsmentioning
confidence: 93%
“…UEDA et al [127] have shown that modifications of lung density at various pulmonary volumes correlated with abnormalities in distal airways and asthma severity. LEE et al [128] showed that centrilobular opacities were more prevalent among subjects with near-fatal asthma, and that these abnormalities were partially reversible after the successful control of asthma symptoms.…”
Section: Assessment Of Distal Airways In Asthma: Imaging High-resolutmentioning
confidence: 99%
“…Regional mosaics of reduced parenchymal density, apparently due to air trapping, are associated with asthma on computed tomography (CT) (8). More recently CT, and especially multi-detector CT (MDCT), have been used to quantitatively measure lung parenchymal density and correlate these measures to obstructive physiology (9,10).…”
Section: Introductionmentioning
confidence: 99%